Experimental Validation of a Numerical Model for the Analysis of Erosion Depth in Coarse Sand Induced by a Dam Break of Water - Cruchaga-Ssa., M; Nunez-Aedo, J; Fuentes-Ortega, B (Elsevier Ltd, 2025)
A computational model for studying the scour depth of coarse sand generated by a dam break is presented and validated using data obtained from an original experiment also reported in this work. The experimental study includes sand characterization. Different aspect ratios for the fluid column heights of the dam break are considered to provide data for evaluating how operating parameters affect the evolution of the free surface (water–air interface) and sand erosion (sand interface). The experiments are video recorded, and the opening speeds of the gate, free surface, and scour depths are measured using image processing techniques from the videos registered. The simulations are performed in the framework of an open-source software with the Smoothed Particle Hydrodynamics method (SPH). The coarse sand is described as a non-Newtonian fluid. A unique set of numerical parameters used in modelling is determined to adequately describe the whole set of cases. The experiments demonstrate that the scour of the sand is affected by the aspect ratio of the dam break. Despite the opening speed of the gate experimentally presenting fluctuations, this aspect does not affect the scour of sand in the speed range analysed. The results show that the scour depths of the studied sand increase as the aspect ratio increases. These experimental facts are also observed from the numerical analysis. Moreover, a good statistical agreement is obtained between experimental data and the numerical predictions for the free surface and the scour depth evolutions. These allow us to validate the proposed three-dimensional numerical model. © 2025 Elsevier Ltd
Keywords: Scour depth study; Numerical and physical models; Experiments; Validation of simulations; Model parameters definition; Statistical analysis